neekalia
neekalia
02-12-2021
Mathematics
contestada
not sure how difficult this would be to solve
Respuesta :
augustinethawnpi
augustinethawnpi
02-12-2021
f (x) = x^2 - 2x + 1
f (x) = (-2)^2 - 2(-2) + 1
= 4 + 4 + 1
= 9
f (x) = ( 0 )^2 - 2 (0) + 1
= 0 - 0 + 1
= 1
0 = x^2 - 2x + 1
x^2 = 2x - 1 = 1
f (2) = 2^2 - 2(2) + 1
= 4 - 4 + 1
= 1
f (3) = 3^2 - 2(3) + 1
= 9 - 6 + 1
= 3 + 1
= 4
Answer Link
VER TODAS LAS RESPUESTAS ( 64+ )
Otras preguntas
Which entrepreneur named below took over and expanded a family business begun by his or her father?
Everyone who shares a respective ethnic identity expresses that identity through the same ethnic work. a. True b. False
What type of figurative does this sentence use "the shadows loomed again"
Obscenity is derived from the latin word caenum that means
Which country was still controlling vietnam as a colony following would world war 2?
Build a rectangular prism using cubes. Then, draw in your journal the top, side, and bottom views of your prism.
Ellen is taking some friends on a picnic. They'll need to follow a path to get the picnic spot. A map of the path is based on a scale of 1 : 10,000 , in cm. If
A multi-issue interest group is an interest group that is primarily concerned with __________.
What does the air tube do on a grasshopper?
Which of the following helped revive the economy of Carbon Hill? the TVA the HOLC the AAA the WP